2023
DOI: 10.1257/aer.20211127
|View full text |Cite
|
Sign up to set email alerts
|

What Happens When Employers Can No Longer Discriminate in Job Ads?

Abstract: When employers' explicit gender requests were unexpectedly removed from a Chinese job board overnight, pools of successful applicants became more integrated: women's (men's) share of callbacks to jobs that had requested men (women) rose by 61 (146) percent. The removal “worked” in this sense because it generated a large increase in gender-mismatched applications, and because those applications were treated surprisingly well by employers, suggesting that employers' gender requests often represented relatively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Occupational sorting may also be related to systematic differences between men and women in the attitudes towards risk or competition, though the evidence is mixed in this respect (Eckel and Grossman, 1996, Holt and Laury, 2002, 2005, Gneezy et al, 2003, Vandegrift and Yavas, 2009, Bertrand, 2011. Additionally, several studies have shown that also employers are likely to contribute to gender occupational segregation as they prefer to hire women in female-dominated occupations and men in male-dominated occupations (Becker et al 2019, Kuhn et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational sorting may also be related to systematic differences between men and women in the attitudes towards risk or competition, though the evidence is mixed in this respect (Eckel and Grossman, 1996, Holt and Laury, 2002, 2005, Gneezy et al, 2003, Vandegrift and Yavas, 2009, Bertrand, 2011. Additionally, several studies have shown that also employers are likely to contribute to gender occupational segregation as they prefer to hire women in female-dominated occupations and men in male-dominated occupations (Becker et al 2019, Kuhn et al 2023.…”
Section: Introductionmentioning
confidence: 99%